Plasticity-induced stacking fault behaviors of γ' precipitates in novel CoNi-based superalloys. (10th November 2021) - Xu, W.-W.; Yin, G.H.; Xiong, Z.Y.; Yu, Q.; Gang, T.Q.; Chen, L.J.
Highlights: Stacking fault energies of γ' precipitates in Co-based superalloys are computed. Strong dependence of stacking fault behaviors on the composition is discussed. Excessive either ni or w deteriorates the strength even the stability of γ' phase. The ΔEp value bridges GSFE barriers and plastic mechanisms at elevated temperatures. Grain orientation also governs the plastic deformation in the Co-based superalloys. Abstract: Implementation of novel γ/γ' Co-based superalloys with higher strength and improved creep durability is a challenging task for researchers. The lack of atomic-level understanding of plastic deformation behavior has seriously limited the exploration of the full capacity of Co-based alloys. We put forward a comprehensive study of generalized stacking fault energies by first principles to explore the effect of Ni and Al/W on the plastic deformation mechanism of γ' precipitates in Co-based superalloys. It is found that alloying Ni and adjusting Al/W obviously change the dislocation glide and twinning nucleation in the γ' precipitates by altering the stable fault energies and the unstable fault energy barriers. Excessive addition of either Ni or W deteriorates the strength even the stability of alloys. The ratio of effective planar fault energy (Δ E p ) bridges intrinsic energy barriers and various deformation mechanisms of superalloys at elevated temperatures. Except for alloying effects, the grain orientation also significantly governs the operation of the plastic deformation of superalloys. Our theoretical results agree with the available measurements and well capture the observed phenomena in experiments.